Uma nova visão estrutural dos vidros fosfatos - Araújo, Dráulio Barros (1997)
X-Rays diffraction, A.C. and D.C. conductivity, differenctial thermal analysis and infrared and 57Fe Mössbauer spectroscopies were used to investigate a family of semicon ductive phosphate glasses given by the formula xMnO — 60P205— (40 — x)Fe203 where x ranges from 0 to 40 mol%. The vitreous character of all the samples were confirmed by x-rays diffraction analysis. The room temperature (300K) Mössbauer spectra revealed the presence of both Fe+2and Fe+3 ions in all the samples. The isomer shift(δ ) values obtained at 300K show primarily that the Fe+3 ions are at sites of distorted octahedral symmetry (NWM) (0.35mm/s ≤ δ ≤ 0.55mm/s), whereas the Fe+2 ions occupy both sites of distorted thetrahedral (NWF) (δ ≤ 1.00mm/s) and octahedral (NWM) (δ ≥ 1.00mm/s) coordination. Through the temperature dependence of the Mössbauer parameters isomer shift, quadrupole splitting and f-factor, that are related to the Debye temperature (ϴD) of the Mössbauer ions, we confirm the local structure of the iron ions. The results suggest that Mn and Fe ions substitute each other at interstitial sites acting as NWM. The infrared spectroscopy results show that the increase of the Fe content in the samples increases their stability and are in full agreement with the M6ssbauer results. The D.0 electrical conductivity measurements reveal the semiconductive nature of the samples and show that the ratio Fe+2/Fe+3.